The impact of the “economy of history”: The example of battlefield tourism in France - David Foulk (Mondes du Tourisme, 2016)
The “economy of history” in France, or history as a motor for French economic activity, is of great importance to those areas of the country most affected by the First and Second World Wars. The attraction of France to tourists is a well-known, and quantifiable, phenomenon, yet the impact of battlefield tourists on both the local and national economies has remained hitherto unknown. Battlefield tourism attracts enthusiasts both from within France’s borders, as well as those journeying from further afield. This study seeks to show the relative importance of this niche market for those French villages that have been the most heavily touched by these historical events, making use of both official statistics as well as those published by the centres themselves, most notably the Historial de la Grande Guerre at Péronne and the Visitor Centre at Thiepval. However, the economic consequences are not simply felt within France, but also cross international borders along with those undertaking the journey, illustrated by the case study of Leger Holidays.